THE ROLE OF THE SOCIAL AND INNOVATION FACTOR IN THE INTERESTS OF YOUTH AND BALANCING THEM - Otamuratov, Sarvar (International Journal of Psychosocial Rehabilitation, 2020)
The whole essence of interests began with human consciousness, which is the only one of the most pressing issues in the entire system of social relations. It is becoming more and more relevant for the development of the minds and intellectual abilities of people, and today it serves, on the other hand, it has become a very terrible factor in the emergence of various conflicts and massacres. Because they are a necessary basis for and the driving force of peoples and countries to live, survive and thrive. The interests can be categorized as the individual interests of each individual and individual, national, social groups, classes, political forces, interests of the state, society, common interests of nations, states, and the common interests. Each of them has its own "internal" structure. That is, the interests of subjects are represented in several areas. By looking at their examples as national or social groups, we can clearly see the meaning of the specific "internal" structure mentioned above. Thus, the interests of young people are varied and can be divided into two private (private) and general groups. When private interests are concerned with the outlook, tendencies and interests of each age group, the common interests are related to such notions as the motherland, the homeland, the land of ancestors. It should be noted that private (personal) interests of young people are formed on the basis of common interests.